Carotid endarterectomy in the setting of persistent hypoglossal artery - Samuel D. Leonard, MD; Lili Sadri, MD; Hung Nguyen, MD; Naveed Saqib, MD; Marvin Heck, MD; Gordon Martin, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Persistent hypoglossal artery (PHA) is a rare, anatomical variant in which the posterior cerebral circulation is primarily supplied by a branch of the carotid artery, rather than the vertebral arteries. This case report discusses carotid endarterectomy performed on a man, 67 years of age, with high-grade, asymptomatic carotid artery stenosis and ipsilateral PHA. Preoperative computed tomography angiography identified the PHA arising from the internal carotid artery, compensating for atretic bilateral vertebral arteries and providing primary perfusion to anterior spinal artery. A carotid endarterectomy with a bovine pericardial patch was executed under general anesthesia, incorporating preemptive shunting of the PHA and intraoperative electroencephalogram monitoring. The operation proceeded without complications, maintaining normal electroencephalogram readings, and the patient exhibited no focal neurological deficits postoperatively, although transient dysphagia was noted. Follow-up imaging at 4 months confirmed the patency of the internal carotid artery and PHA. This case underscores the necessity for meticulous surgical planning and monitoring in the presence of rare vascular anomalies to ensure successful outcomes. The key takeaway is that comprehensive, preoperative imaging, individualized surgical strategies, and vigilant postoperative monitoring are critical for managing rare vascular anomalies, such as PHA.